PERBEDAAN PERSEPSI, KEPERCAYAAN DAN LOYALITAS NASABAH DALAM INDUSTRI PERBANKAN - Andespa, Roni (Imara: JURNAL RISET EKONOMI ISLAM, 2018)
AbstractThis article has the theme: "Sharia Business Management". The purpose of this research is to see the difference between perception, trust and loyalty of conventional bank customers with sharia bank customers in West Sumatera on attributes of deposit products and loan products. This research was conducted in West Sumatera. The research variables are customer perception, customer trust and customer loyalty. The sample is 250 conventional bank customers and 250 sharia bank customers. Analysis of research data using independent samples t-test. The result of research are: 1) There is difference of perception between conventional bank customer with syariah bank to attribute of product, 2) There is difference of trust between conventional bank customer and syariah bank to product attribute 3) There is difference of loyalty between conventional bank customer with sharia banks against product attributes.Keywords: Customer perception, Customer trust, Customer loyalty, Product attributes